Improvement of Pitch Motion Control of an Aircraft Systems - Aishah Johari; Fitri Yakub; Hatta Ariff; Zainudin A. Rasid; Shamsul Sarip; Rudzidatulm Akmam Dziyauddin; Mohd Zamzuri Ab Rashid; Azizul Azizan; Yasuchika Mori (Universitas Ahmad Dahlan, 2018)
The movement of the aircraft pitch is very important to ensure the passengers and crews are in intrinsically safe and the aircraft achieves its maximum stability.The objective of this study is to provide a solution to the control system that features particularly on the pitch angle motion of aircraft systemin order to have a comfort boarding. Three controllers were developed in these projects which wereproportional integral derivative (PID), fuzzy logic controller (FLC), and linear quadratic regulator (LQR) controllers. These controllers will help improving the pitch angle and achievingthe target reference. By improving the pitch motion angle, the flight will be stabilized and in steady cruise (no jerking effect), hence provides all the passengers withthe comfort zone. Simulation results have been done and analyzed using Matlab software. The simulation results demonstrated LQR and FLC were better than PID in the pitch motion system due to the small error performance. In addition, withstrong external disturbances, a single controller is unable to control the system, thus, the combination of PID and LQR managed to stabilize the aircraft.